REGIONAL THEORETICAL AND PRACTICAL CONFERENCE «TIMELY PEDIATRIC PROBLEMS» - A.A. Автор (Вопросы современной педиатрии, 2011)
(Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 176–177.)